2011
DOI: 10.1111/j.2044-8295.2011.02031.x
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and ease of ambiguous figural reversal

Abstract: Two studies examined the relationships between self-rated and objectively measured creative ability and ease of perceiving alternative interpretations of the ambiguous Duck-Rabbit figure. The studies found empirical support for what has previously been a largely analogical connection between figural reversal and creativity, using both self-rated trait creativity and objectively scored creative productivity. We discuss the hypothesis that executive functioning is the likely common cognitive factor linking perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 23 publications
5
47
1
2
Order By: Relevance
“…The findings in the current study partly support the findings of Wiseman et al (2011), who found that MI acuity was linked to both self-perceived trait creativity and objective measures of creative flexibility and fluency. In the current study vivid MI did not relate to objective measures of performance, including transformational complexity, which is theoretically a measure of structural reconfiguration and agility.…”
Section: Feedback Ambiguity Congruence and MI Vividnesssupporting
confidence: 81%
See 1 more Smart Citation
“…The findings in the current study partly support the findings of Wiseman et al (2011), who found that MI acuity was linked to both self-perceived trait creativity and objective measures of creative flexibility and fluency. In the current study vivid MI did not relate to objective measures of performance, including transformational complexity, which is theoretically a measure of structural reconfiguration and agility.…”
Section: Feedback Ambiguity Congruence and MI Vividnesssupporting
confidence: 81%
“…Studies have since provided evidence that there is spatial and temporal equivalence between mental and perceptual imagery (Finke, 1980), that restructuring and reconstrual does frequently occur, and that geometric data are preserved in MI to allow new categorical interpretations to be formed (Finke, Pinker, & Farah, 1989;Mast & Kosslyn, 2002;Peterson, Kihlstrom, Rose, & Glisky, 1992). Wiseman, Watt, Georgiou, and Gilhooly (2011) showed that creative ability was linked to the ability to reinterpret ambiguous mental images mentally, confirming that agility in internally manipulating imagery is a fundamental component of creativity. Beethoven and Monetdeaf and blind, respectively, when they created some of their most famous masterpieces -and Einstein -who carried out many thought experiments using only his imagination -exemplify in a real-world context that notable creativity does occur without access to or use of perceptual faculties (Garland-Thomson, 2005;Ghiselin, 1952;Harrison, 1988).…”
Section: Creative Performance With MI and Sketchingmentioning
confidence: 74%
“…For example, in Experiment 2 the first phase duration for image D2 (street map-flag pole, see Figure 5) is longer than for other images in the same experiment, suggesting that this image is processed differently. Previous studies that examined the connection between creativity and perceptual switching overlooked the role of different types of images (Doherty & Mair, 2012;Laukkonen & Tangen, 2017;Wiseman et al, 2011;Wu et al, 2016). It is possible that the relation between perceptual switching and creativity is found only for some images.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have empirically investigated the relationship between the two phenomena. Wiseman, Watt, Gilhooly, and Georgiou (2011) provided empirical support for the connection between perceptual switching and divergent thinking or, in general, creative ability: participants who reported that they could switch more easily to the second interpretation of the Jastrow duck-rabbit image also rated themselves as being more artistically creative and better creative problem solvers. They also found a strong correlation between self-reported ease of perceptual switching and categorical flexibility measured with a single item unusual uses task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation